Penerapan Model Mind Mapping dalam Pembelajaran Sejarah Kebudayaan Islam di MIN 2 Padang Pariaman - Rahmanita Rahmanita; M. Yusuf (Mau'izhah, 2021)
The purpose of the study was to find out how thelearning process of Islamic Cultural History after theimplementation of the mind mapping model or concept mapand what were the supporting factors in the application of themind mapping model or concept map in learning IslamicCultural History at MIN 2 Padang Pariaman Regency. Thisresearch is a qualitative field research using a descriptivemethod, namely by describing the object of research as it is.The sources of data in this study were the Head of Madrasah,teachers of Islamic Cultural History, and students. While thedata collection techniques used are observation, interviews anddocumentation. The data that has been collected is thenprocessed by means of data reduction, data presentation anddrawing conclusions. From the results of the study, it wasfound that based on the analysis of the syntax of the mindmapping model or concept map at Madrasah Ibitidaiyah Negeri(MIN) 2, Padang Pariaman Regency, it had been implementedwell but did not match perfectly with the mind mapping theory.There are still some shortcomings, namely mind mappingtheory is a learning model that seeks to make students moreactive than the teacher while the learning process takes placenot many students are active to answer or ask the teacher aboutthe material being studied. The supporting factor in the application of the mind mapping model in learning IslamicCultural History at Madrasah Ibtidaiyah Negeri (MIN) 2Padang Pariaman Regency is the support of the Madrasah Headwho supports the application of the mind mapping model andthe teacher or educator who is the key to the success of thelearning process and parental attention. The obstacle in theapplication of the mind mapping model or concept map inlearning Islamic Cultural History at Madrasah IbtidaiyahNegeri (MIN) 2 Padang Pariaman district is the source bookwhich is not enough funds, there is only one source book.